Short-term safety profile of COVID-19 vaccination in children and adolescents with underlying medical conditions: a prospective cohort study - Naye Choi; Seung-Ah Choe; Yo Han Ahn; Young June Choe; Ju-Young Shin; Nam-Kyong Choi; Seong Heon Kim; Hee Gyung Kang (Korean Society of Pediatric Nephrology, 2023)
Purpose This article was to collect data on the safety of coronavirus disease 2019 (COVID-19) vaccines in children with underlying medical conditions. Methods We constructed a prospective cohort of children and adolescents aged 5 to 19 years who had received at least one dose of COVID-19 vaccine. Patients diagnosed with and treated for chronic kidney disease, autoimmune disease, or other chronic conditions at the Seoul National University Children's Hospital were recruited from June to December 2022. A mobile survey questionnaire was sent to their guardians. The presence of adverse events on the day (day 0), 3 weeks (day 21), and 6 months (day 180) after the 1st dose of COVID-19 vaccine was recorded by the guardians. Results A total of 73 children participated. The median age was 14 years, and 64.4% of the patients were male. On the day of immunization, 65.8% of the patients reported at least one adverse event. Pain at the injection site, fatigue, headache, arthralgia, and myalgia were the most common symptoms. The prevalence of adverse events decreased over time (65.8% on day 0, 27.4% between days 0 and 21, and 24.6% between days 21 and 180). Severe acute respiratory syndrome coronavirus 2 infection after the 1st dose occurred in 17 patients (23.3%) and one of the patients (5.88%) was hospitalized due to infection. Conclusions Adverse events after COVID-19 vaccination were generally mild in children and adolescents with underlying medical conditions. Our findings provide evidence for the safety of COVID-19 vaccination in the vulnerable pediatric population.